2007
DOI: 10.1093/ps/86.4.691
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nutrient Density on Performance, Egg Components, Egg Solids, Egg Quality, and Profits in Eight Commercial Leghorn Strains During Phase One

Abstract: This study was a 3 x 8 factorial arrangement of 3 nutrient densities (low, medium, and high) and 8 commercial Leghorn strains. The objective of this experiment was to determine the effect of increasing both dietary energy and other nutrients (amino acids, Ca, and available P) on performance, egg composition, egg solids, egg quality, and profits in 8 commercial Leghorn strains during phase 1 (from 21 to 36 wk of age). This experiment lasted 16 wk. Eight strains of hens (n = 270 of each strain) at 21 wk of age w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
35
4
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(57 citation statements)
references
References 19 publications
12
35
4
3
Order By: Relevance
“…This may be explained by the higher feed intake of the birds fed higher energy levels, according to the experimental treatments. The results of the present experiment disagree with the findings of Grobas et al (1999), Wu et al (2007) and Valkonen et al (2008), who fed layers different dietary ME levels and observed an improvement (P<0.05) in feed conversion ratio as the dietary ME increased. On the other hand, Grobas et al (1999) and evaluated the effect of the intake of feeds containing different energy levels on the egg production of layers and concluded that feed conversion ratio was not influenced (P>0.05) by the dietary energy level; however, feed was offered ad libitum in these experiments.…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…This may be explained by the higher feed intake of the birds fed higher energy levels, according to the experimental treatments. The results of the present experiment disagree with the findings of Grobas et al (1999), Wu et al (2007) and Valkonen et al (2008), who fed layers different dietary ME levels and observed an improvement (P<0.05) in feed conversion ratio as the dietary ME increased. On the other hand, Grobas et al (1999) and evaluated the effect of the intake of feeds containing different energy levels on the egg production of layers and concluded that feed conversion ratio was not influenced (P>0.05) by the dietary energy level; however, feed was offered ad libitum in these experiments.…”
Section: Resultscontrasting
confidence: 99%
“…There was no influence of the treatments on egg production (Table 5). Similar results were also obtained by , Wu et al (2007), Jalal et al (2007) and Costa et al (2009), who fed layers with different ME levels and concluded that the dietary energy level did not cause any significant effect (P>0.05) on egg production. However, Araújo & Peixoto (2005) observed instead a reduction in egg production (P<0.05) as the dietary energy level increased, whereas Valkonen et al (2008) obtained an increase in egg production with increasing dietary energy levels; however, the latter worked with energy levels lower than those used in the present study and those recommended in the literature (2345 to 2629 kcal ME/kg feed).…”
Section: Resultssupporting
confidence: 87%
“…In other words, the lowest levels of GAA had not significant effects on EW, while the highest levels reduced it. EW is a parameter which affects by diets protein and amino acid level [32] and the arginine role is accepted as increaser the protein synthesis [33] . The mechanism of action is not known.…”
Section: Discussionmentioning
confidence: 99%
“…In both cases, however, the relative weight of the yolk was not changed. In an experiment with Leghorn hens, increased dietary levels of energy and amino acids signifi cantly increased egg weight (Wu et al, 2007).…”
Section: Discussionmentioning
confidence: 99%